Major milestone achieved for measuring methane and feed intake from free-grazing pastoral cattle in East Africa - Arndt, Claudia; Mulat, Daniel; Slater, Annabel; Garcia, Edward (International Livestock Research Institute, 2025)
This blog documents the first successful direct measurement of enteric methane emissions and feed intake from free-grazing pastoral cattle under real rangeland conditions in East Africa. By adapting internationally recognised measurement approaches to extensive grazing systems, the work generates region-specific data needed to improve national greenhouse gas inventories and to design mitigation strategies that are relevant for pastoral livestock systems.